Self s-doped porous carbon from polyphenylene sulfide: Kinetic and thermodynamic study of co2 adsorption and separation performance - Afdhal, Junaidi; Dini Nirmala, Nilamsari; Nareswari, Cininta; Norazlianie, Sazali; Gunawan, Triyanda; Widiastuti, Nurul (Elsevier, 2025)
Porous carbon derived from polyphenylene sulfide (PPs), which is enriched with sulfur functionalities, emerges as a highly promising material for the adsorption of CO2, due to its polar and acid-base interactions. While prior studies have explored its potential as an S-doped carbon adsorbent, a comprehensive understanding of its gas adsorption behavior and separation performance remains limited. This study explores the adsorption kinetics, thermodynamics, and gas separation performance of self S-doped porous carbon from PPs (PCs) for CO2, CH4, and N2 gas, both as a distinct adsorbent and as a filler in mixed matrix membranes (MMMs). The porous carbon was synthesized through a one-step activation process utilizing potassium carbonate (K2CO3) resulting in a high surface area of 2023 m2/g and a CO2 uptake of 4.59 mmol/g at 30 °C. Adsorption kinetic modeling and thermodynamic analysis confirm favorable CO2 adsorption mechanisms compared to CH4 and N2. Furthermore, the addition of PCs to hollow fiber membranes significantly enhanced CO2 permeability, increasing it from 7.64 GPU to 67.49 GPU while maintaining CH4 and N2 permeability, leading to improved selectivity. These findings highlight the critical role of S-doped carbon fillers in enhancing both adsorption efficiency and membrane-based gas separation, offering new insights into their interaction mechanisms and practical applications in CO2 capture and separation.